Impact of Internal Control System in Preventing, Detecting Accounting Frauds and Errors in Educational Institutions of Khotang District, Nepal - Rai, Harka Bir (DMC Journal, 2024)
The purpose of this study is to ascertain how internal controls affect fraud, Error detection and prevention in public and private schools. The descriptive research method is applied. Primary data were employed in this study, and a questionnaire with points Likert Scale instrument was used to gather the data. Accountants, Head Teachers, the Chairperson of the school management committee, Teachers and Auditors from the 96 secondary schools in the Khotang District make up the population. By utilizing a random sampling technique, 55 respondents were chosen. This study employs both descriptive and inferential analytical techniques. The study's findings demonstrated the critical role internal control plays in identifying and preventing fraud, error. The study discovered that fraud prevention and detection strategies at both public and private schools are positively and significantly impacted by each of the five internal control components. The five internal control components that make up the independent variables and the dependent variable fraud prevention and detection were found to be strongly positively correlated. There is a strong correlation between the control environment, risk assessment, control activities, information and communication, monitoring activities, fraud, error detection, and prevention. The result shows the strong positive correlation of five internal components are 0.993, 0.982, 0.911, 0.944, and 0.957. This suggests that strengthening an internal control system component will strengthen fraud, error detection and prevention. Furthermore, it is proposed that the effective application of the internal control system in preventing and detecting fraud in schools is hampered by human error, management override, failures, and cooperation between internal and external parties.